Contradiction Belief on COVID-19 among Academia: A Lesson for the Future Pandemic Management - Maulana Ikhsan; Muhammad Syahriza; Tischa Rahayu Fonna; Baluqia Iskandar Putri (HM Publisher, 2022)
Health protocol during the COVID-19 pandemic is one of the critical protocols against the pandemic. However, after more than one year, compliance with implementing this protocol is still a shortcoming. The overabundance of information, in particular hoaxes and misinformation, is accused of being the elemental reason why that disbelief exists even after one year apart. The World Health Organization even put hoaxes and misinformation as one of the current world health challenges in the modern era. This study aims to observe the perception of academia at Universitas Malikussaleh towards the COVID-19 pandemic. This study also scrutinizes the depiction of COVID-19 health protocol among its correlation to COVID-19 disbelief. We found that there is a cognitive dissonance among the academia who believe that the COVID-19 pandemic exists. This cognitive dissonance makes their action contradict their belief, in particular, the implementation of health protocol and its benefit to protect themselves and other people.